Acute Decompensated Heart Failure (ADHF) with aortic dissection Stanford A in middle aged man: a case report - Anbiya Khairul Umam; Ida Bagus Wisnu Widiarta; Marwa Humaira Intizam; Aizar Vesa Prasetyo; Ketut Putu Yasa (Intisari Sains Medis, 2021)
Background: Heart failure is a clinical syndrome with shortness of breath, fluid retention, and the heart's structural and functional disorder. Each year, there were 7,2 cases every 1000 people on male and 4,7 cases every 1000 people on the female. Aortic dissection is an emergency disease in which the symptoms are similar to ischemic heart disease, that 38% of patients got misdiagnosed on the first evaluations. Because of the clinical course of heart failure and misdiagnosed aortic dissection that frequently happened, authors are interested in making a case report with both conditions.Case report: A male patient, 39 years old, complained of shortness of breath and epigastrium pain. The patient was diagnosed with Acute Decompensated Heart Failure (ADHF) profile B with emergency hypertension and suspected aortic dissection based on history and physical examination. The patient was also diagnosed with acute kidney injury stage 1. CT angiography showed widening of the aorta ascending until arcus aorta with a Stanford type A aortic dissection diagnosis.Conclusion: The condition of aortic dissection can coincide with acute heart failure. Therefore, a clinician must be aware of the emergency of dissection and know the initial symptoms of dissection. The typical clinical symptoms of dissection lead us to perform imaging studies that ultimately lead to a thoracoabdominal CTA to diagnose the dissection.